SAFETY OF CARBON FIBRE REINFORCED PLASTIC HOLLOW SECTIONS IN COMPRESSION (Nigerian Journal of Technology, 2016)
The use of steel hollow sections as compression members in structures has been a common practice. This study highlights the safety of using Carbon Fibre Reinforced Plastic (CFRP) hollow sections as compression structural members. The primary compression members in structures are columns and this study uses Finite Element Analysis (FEA) to investigate the effects of pure axial compressive loads on CFRP hollow sections. Hollow CFRP columns having different sizes and material thicknesses were modeled using ABAQUS/CAE three-dimensional non-linear finite element analysis and the results obtained are used to measure the deformation under compression. All loads used were Euler’s critical buckling load. Steel hollow sections were also designed using the same method. This serves as a basis of comparison for a number of factors such as material thickness, section shape, deformation scale factor, size of cavity and length effect that will ultimately affect the deformation and failure of columns under axial compressive loads. Results show that at critical axial loads there is no considerable buckling at mid-height for CFRP hollow sections and steel hollow sections. Analysis of results from ABAQUS/CAE concluded that for most cases under critical loading, CFRP hollow sections shorten in length and increase in lateral dimension; this explains the growing trend of using CFRP hollow sections as confinement for reinforced concrete columns, given that concrete is good in compression. For axial compressive loads less than the critical loads, CFRP hollow sections are generally safe. http://dx.doi.org/10.4314/njt.v35i4.8